Pathophysiology of Meibomian Glands – An Overview. (19th May 2021) - Dietrich, Jana; Garreis, Fabian; Paulsen, Friedrich
ABSTRACT: Purpose : The meibomian glands are located in the tarsal plate of the upper and lower eyelid and are responsible for the production of a lipid-rich secretion, the meibum, which forms the outer component of the tear film. Meibomian gland dysfunction results in excessive evaporation of the tear film and is the leading cause of dry eye disease (DED). Despite the high prevalence of DED, the etiology of meibomian gland dysfunction is only basically understood. In addition, the molecular mechanisms of meibomian gland maturation and physiological function are currently the focus of research. Methods : A systematic literature search was performed using the main scientific databases, including all relevant published articles up to September 2020. Results : This article provides an overview of the current state of knowledge about meibomian gland stem cells, cell surface marker expression and PPARγ signaling, as well as the pathological causes of meibomian gland dysfunction. Conclusion : Androgen deficiency, hyperkeratinization, PPARγ signaling and inflammatory reactions including neutrophil extracellular traps (NETs) seem to be key factors within the pathological processes of the meibomian gland.